Augustine and the Catechumenate - Harmless, William; Fitzgerald, Allan (Liturgical Press, 2014)
Intro -- Titlepage -- Copyright -- Dedication -- Contents -- List of Charts -- List of Abbreviations -- Foreword -- Preface to the Revised Edition -- INTRODUCTION To Return to the Sources -- What the RCIA Says -- What the RCIA Implies -- What the RCIA Does Not Say -- The Investigation -- CHAPTER ONE The Fourth-Century Catechumenate -- Third-Century Inheritances: North Africa -- The Catechumenate: Trends in the Greek East -- Lent: Trends in the Greek East -- Mystagogy: Trends in the Greek East -- CHAPTER TWO Augustine and the Catechumenate in Milan -- Augustine the Catechumen -- Augustine the Petitioner -- Augustine the Neophyte -- Lessons from the Threshold -- CHAPTER THREE Evangelization: Unrolling the Scroll -- The Candidate: Milieu, Motives, and Types -- The Catechesis: Principles -- (1) The Classical Background -- (2) The Narrative: Making the Case for Christianity -- (3) Exhortation and End Time -- The Catechist: Cultivating Delight -- The Catechesis: Examples -- The Message and the Messenger -- CHAPTER FOUR Catechumenate: Breaking Open the Bread of the Word -- Feeding the Hungry: The Liturgy of the Word -- Noisy Improvisations: The Sermon and Its Hearers -- (1) Written Text and Oral Performance -- (2) Audience Response -- (3) The Disciplina Arcani -- A Seasoned Rhetoric: The Method -- Scripture and Its Riddles: The Core Curriculum -- Conversi ad Dominum: The Dismissal -- Excursus: The Delay of Baptism? -- CHAPTER FIVE Catechumenate: The Eagle and the Staircase -- Two Sessions: December 406 -- Tractate on John -- Exposition of Psalm -- Melodic Themes -- (1) The Paradox of Christ -- (2) The Church as Body of Christ -- (3) Baptism and the Donatists -- (4) A Spirituality for Exiles -- Turning to the Catechumens -- Tractate 3 -- Tractate 4 -- Tractate 10 -- Tractate 11 -- Tractate 12 -- Theater of the Word -- CHAPTER SIX Lent: Time in the Womb